2017
DOI: 10.1186/s40463-017-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for head and neck cancer of unknown primary including the impact of human papilloma virus infection

Abstract: BackgroundHead and neck cancer of unknown primary (HNCUP) is rare and prospective studies are lacking. The impact of different prognostic factors such as age and N stage is not completely known, the optimal treatment is not yet established, and the reported survival rates vary. In the last decade, human papilloma virus (HPV) has been identified as a common cause of and important prognostic factor in oropharyngeal cancer, and there is now growing interest in the importance of HPV for HNCUP. The aim of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
4
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 33 publications
9
69
4
3
Order By: Relevance
“…Keller et al [58] reported on even more pronounced survival differences in p16 positive compared to p16 negative patients (5y OS 92% vs 30% and 5y DSS 92% vs 60%) [58]. Similar results were demonstrated by Jensen et al [57], Schroeder et al [27] and Axelsson et al [64], whereas Tribius et al [55] and Dixon et al [65] did not find any survival difference. In contrast to some [1,2,27,[66][67][68] but in line with other reports [54,56] nodal stage did not have an impact on survival in our cohort.…”
Section: Discussionsupporting
confidence: 69%
“…Keller et al [58] reported on even more pronounced survival differences in p16 positive compared to p16 negative patients (5y OS 92% vs 30% and 5y DSS 92% vs 60%) [58]. Similar results were demonstrated by Jensen et al [57], Schroeder et al [27] and Axelsson et al [64], whereas Tribius et al [55] and Dixon et al [65] did not find any survival difference. In contrast to some [1,2,27,[66][67][68] but in line with other reports [54,56] nodal stage did not have an impact on survival in our cohort.…”
Section: Discussionsupporting
confidence: 69%
“…68 Adjuvant CRT was administered in four patients (three RT and one CRT) in case of positive margins, extranodal extension, multiple positive lymph nodes, perineural invasion, or lymphovascular invasion. 24 Outcome analysis demonstrated similar 2-, 5-, and 10-year OS (93%, 89%, and 89% vs 90%, 90%, and 80% in the two groups, respectively). 68 Neck dissection is a common practice but should be reconsidered in the light of RT advances as outcomes were independent of neck dissection in some studies.…”
Section: Surgical Diagnostic Procedures and Neck Dissectionmentioning
confidence: 75%
“…6,16,17,20 The male predominance correlates with the ease of female-to-male HPV transmission which is precipitated by the high number of sexual partners and oral sex encounters. 16,17,19,20,[22][23][24] However, one retrospective analysis of a small series of patients showed that the HPV status does not correlate with neck stage at presentation. The clinical N classification at diagnosis is usually N2/N3 (11%-95%).…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations